2006
DOI: 10.1097/00004850-200607000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic acid accelerates the antidepressant effect of fluoxetine in the chronic escape deficit model of depression

Abstract: Evidence has accumulated suggesting that major depression is associated with dysfunction of inflammatory mediators. Moreover, antidepressants show an anti-inflammatory action possibly related to their clinical efficacy. An improvement in psychiatric symptoms has been recently reported in patients treated with anti-inflammatory drugs for other indications. These data imply that inflammation may be involved in the pathogenesis of depression and that anti-inflammatory drugs may be used as an adjunctive therapy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 56 publications
2
66
0
1
Order By: Relevance
“…In addition, the bi-directional crosstalk between SSRI administration and inflammation has been described also by studies investigating the effects of antiinflammatory drugs on antidepressant efficacy. Indeed, experimental and clinical studies have shown that anti-inflammatory drugs, such as celecoxib or aspirin, can either improve (Akhondzadeh et al, 2009;Andrade, 2014;Brunello et al, 2006) or impair treatment outcome (Warner-Schmidt et al, 2011). …”
mentioning
confidence: 99%
“…In addition, the bi-directional crosstalk between SSRI administration and inflammation has been described also by studies investigating the effects of antiinflammatory drugs on antidepressant efficacy. Indeed, experimental and clinical studies have shown that anti-inflammatory drugs, such as celecoxib or aspirin, can either improve (Akhondzadeh et al, 2009;Andrade, 2014;Brunello et al, 2006) or impair treatment outcome (Warner-Schmidt et al, 2011). …”
mentioning
confidence: 99%
“…Rahola (2012) also reported that aspirin adjacent to antidepressants significantly improved depression symptoms (38). Another study also reported the effectiveness of fluoxetineaspirin in alleviating depression symptoms (39). Savitz et al (2012) also conducted a study on 120 patients with bipolar disorder who were in depressive phase, and found that aspirin significantly reduced the side effects of antidepressants and significantly improved depression symptoms (36).…”
Section: Discussionmentioning
confidence: 99%
“…Del mismo modo, la aspirina aceleró el comienzo de la acción de la fluoxetina de 3 semanas a sólo 1 en ratas estudiadas utilizando un modelo de depresión consistente en cuantificar las fallas de escape ante situaciones aversivas. Las ratas pretratadas con aspirina evitaban significativamente mejor estímulos dolorosos luego de una semana de la administración de fluoxetina con aspirina, comparadas con aquellas tratadas con aspirina o fluoxetina solamente (Brunello 2006).…”
Section: Investigaciones Nuevas -El Rol De Los Agentes Antiinflamatoriosunclassified